Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1152/ajpgi.00058.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of leukocyte recruitment in postischemic liver microcirculation

Abstract: Evidence shows that leukocyte recruitment into inflamed liver sinusoids does not require selectins, with one notable exception: ischemia-reperfusion (I/R). We used intravital microscopy to directly visualize the liver microcirculation during I/R and localized endotoxemia (liver superfused with lipopolysaccharide). General anti-selectin therapy (fucoidan) or anti-adhesion therapy with an antithrombin inhibitor (hirudin) was also used. Many neutrophils rolled and adhered in postsinusoidal vessels and sequestered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 55 publications
0
32
0
4
Order By: Relevance
“…A recent report by Kubes et al 16 provided an explanation for these contradictions. They convincingly showed that reduced neutrophil accumulation and tissue protection induced by P-selectin interventions in I-R models are secondary effects caused by gut protection, rather than directly related to mechanisms in the liver.…”
Section: Discussionmentioning
confidence: 97%
“…A recent report by Kubes et al 16 provided an explanation for these contradictions. They convincingly showed that reduced neutrophil accumulation and tissue protection induced by P-selectin interventions in I-R models are secondary effects caused by gut protection, rather than directly related to mechanisms in the liver.…”
Section: Discussionmentioning
confidence: 97%
“…When ischemia-reperfusion was performed exclusively in the liver (intestine was removed), the results suggested that the liver was quite resistant to this insult. Only a small amount of leukocyte recruitment was noted in postischemic liver, and antiselectin therapy had minimal effects in sinusoids (17).…”
Section: Targeting Neutrophilsmentioning
confidence: 96%
“…By contrast, an important role for selectins in liver in ischemia-reperfusion has been reported, and substantial numbers of leukocytes adhere in both the postsinusoidal and the sinusoidal venules (17). Because the majority of blood that perfuses the liver initially drains the intestine, ischemia-reperfusion of the liver would also have induced ischemia-reperfusion in the intestine.…”
Section: Targeting Neutrophilsmentioning
confidence: 99%
“…However, during I/R, a number of interventions directed against selectins reduced hepatic neutrophil accumulation and cell injury . Because these findings cannot be explained by the prevention of P-selectin-dependent rolling in sinusoids, it has been suggested that most liver I/R models include some degree of intestinal ischemia, which leads to neutrophil accumulation in remote organs including the liver Kubes et al, 2002). Thus the lower number of neutrophils in the liver when selectins are blocked may be a secondary effect due to the protection of antiselectin therapy against intestinal reperfusion injury ( Kubes et al, 2002).…”
Section: Neutrophil Accumulationmentioning
confidence: 99%